Sustainability in vernacular architecture: the putucos in Puno - Miranda North, Rossana (2009)
The Putucos are an expression of vernacular architecture, rural cultural event in Puno, constructed with blocks of champa, adobe and wood reinforcements. This is a form of recycling, everything is reused, the rare earth elemmts are left on the ground altiplanic which are integrated and the remains of wood used for cooking. The Putucos represent a response and adaptation to the climate of the poorest, who without the help of professional architects and engineers to meet the basic needs of every human need of shelter against inclemnent weather and food. We must understand that these buildings are expressions of a simultaneous need for survival; expressed as a spontaneous and instinctive architecture, whose unique shapes are part of the altiplanic landscape. Are sustainable, since they represent a good example of harnessing solar energy and recycling of nalural materials from the earth and the residues of which are incurred to the same land. Putucos are symbols of the Pemvian highlands, high value and shows that the ancestral architecture must endure and make us rejlect on the best qualities of beauty and rationality in a physical environment and climate of extreme conditions for a population with limited resources, economic constraints and providing solutions to the true survival